Analysis of Social Development and Higher Education Curriculum for Sustainable Development: Issues and Challenges - Fatima, Syeda Tasneem; Sharjeel, Muhammad Yousuf; Fatima, Syeda Aliya (Pakistan Languages and Humanities Review, 2023)
The objective of this study was to examine the impact of SDG curriculum in the aligned context of higher education and o analyze feasibility to incorporate SDG Goals in the curriculum of higher education. The study employed survey research employing a sample of n= 17 higher education faculty members from fours institutions and a sample of n= 28 students in various undergraduate degree programmes. The questionnaire comprised n= 29 items on SDG Goal infusion in the curricula. The results showed that 79 % teachers were seriously interested to incorporate SDG in their professional settings. The study concludes that unless we reform the higher education plans and integrate the contents of SDG Goals, we will not be able to achieve the targets to experience a new world for the next generation. The recommendation is to change the instructions framework, provide sufficient resources in public and private sectors and change the curricula in social sciences courses to adjust SDG goals.